Особливості президентського контролю за діяльністю Національної гвардії України - Байрачна, Т. О.; Bairachna, T. O. (Право і безпека. – 2016. – № 4 (63). – С. 29–34, 2016)
Розглянуто форми здійснення президентського контролю за діяльністю Національної гвардії України. З’ясовано, що специфічність здійснення контролю за діяльністю Національної гвардії України обумовлена її правовим статусом – це військове формування з правоохоронними функціями. На підставі аналізу вітчизняного законодавства визначено засади й особливості здійснення президентського контролю та з’ясовано наявні вади у його правовому регулюванні. Сформульовано пропозиції щодо вдосконалення чинного законодавства.

The object of the research is one of the types of the state control, namely the presidential control over the activities of the National Guard of Ukraine (hereinafter – NGU) and the objective of the paper – is the analysis of existing forms of implementing the presidential control over the activities of the NGU and the development of propositions to improve the legislation on this issue. The relevance and scientific novelty of the proposed conclusions of the article are due to the importance of the presidential control over the military forces activities with law enforcement functions and existence of disputes regarding the scope of powers of the President in the appointment of the commander of the NGU. The main results of the research make it possible to conclude that presidential control over the activities of the NGU is currently carried out both directly by the President of Ukraine, and through the National Security and Defense Council of Ukraine or other specially created institutions by the head of the state. Special attention is paid to the contradictions of the constitutional imperative regarding the appointment of the commander of the NGU. It has been proved that such a situation does not meet the principles of separation of powers in the country. The conclusions of the article suggest to return the rule, under which the commander of the National Guard of Ukraine is appointed and released from the position by Verkhovna Rada of Ukraine identified by the President of Ukraine. The practical significance of the obtained results is that the propositions set in the article are aimed at eliminating existing contradictions in the legislation in regard to the principles of the activities of some subjects of parliamentary control.

Рассмотрены формы осуществления президентского контроля за деятельностью Национальной гвардии Украины. Установлено, что специфичность осуществления контроля за деятельностью Национальной гвардии Украины обусловлена её правовым статусом – это военное формирование с правоохранительными функциями. На основании анализа отечественного законодательства определены принципы и особенности осуществления президентского контроля и выявлены недостатки в его правовом регулировании. Сформулированы предложения по совершенствованию действующего законодательства.
Features of presidential control over the activities of the National Guard of Ukraine
Особенности президентского контроля за деятельностью Национальной гвардии Украины
Байрачна, Т. О.Особливості президентського контролю за діяльністю Національної гвардії України / Т. О. Байрачна // Право і безпека. – 2016. – № 4 (63). – С. 29–34.
Байрачна Т. О. "Особливості президентського контролю за діяльністю національної гвардії України." Право і Безпека 4 (2016): 29-34.
Bairachna, T.O. (2016), “Features of presidential control over the activities of the National Guard of Ukraine” [“Osoblyvosti prezydentskoho kontroliu za diialnistiu Natsionalnoi hvardii Ukrainy”], Pravo i Bezpeka, No. 4, pp. 29–34.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Президент України; військові формування; президентський контроль; Національна гвардія України; Рада національної безпеки і оборони України; командувач Національної гвардії; President of Ukraine; military force; presidential control; National Guard of Ukraine; National Security and Defense Council of Ukraine; Commander of the National Guard; Президент Украины; воинские формирования; президентский контроль; Национальная гвардия Украины; Совет национальной безопасности и обороны Украины; командующий Национальной гвардии